Event history analysis with R - Broström, Göran (Chapman & Hall/CRC the R series (CRC Press), 2012)
With an emphasis on social science applications, Event History Analysis with R presents an introduction to survival and event history analysis using real-life examples. Keeping mathematical details to a minimum, the book covers key topics, including both discrete and continuous time data, parametric proportional hazards, and accelerated failure times.